Influence of counterion type on dielectric and electrorheological responses of poly(ionic liquid)s. (6th December 2017) - Dong, Yuezhen; Liu, Yang; Wang, Bo; Xiang, Liqin; Zhao, Xiaopeng; Yin, Jianbo
Abstract: Different from classic water activated polyelectrolytes, poly(ionic liquid)s (PILs) bearing hydrophobic counterions show high electrorheological (ER) response in dry state. This offers opportunity for practical applications of polyelectrolyte-based ER materials in wide temperature region. For guiding the design of PIL-based ER materials with improved performance, understanding the structure-property relationship is very important. In this paper, a series of poly( p -vinylbenzyl trimethylammonium)-based PIL particles with different counteranions ([PVBTMA][X]) were synthesized with the goal of understanding the role of mobile counterions on ER response of PILs. To exclude particle shape effect, the PIL series were controlled to be monodisperse spheres with a similar diameter via microwave-assisted dispersion polymerization. Under electric fields, the ER response of PIL particles when dispersed in insulating oil was investigated by temperature-modulated rheological test. It showed that the ER response of PILs depends on the type of counteranions. The order of magnitude of ER response of PILs with different counteranion is trifluoromethanesulfonate (TfO − ) > tetrafluoroborates (BF4 − ) > bis-(trifluoromethanesulfonylimide) (TFSI − ) > hexafluorophosphates (PF6 − ). The mechanism behind the influence of counterion type on ER response was analysed by dielectric relaxation spectroscopy. It demonstrated that the influence of counteranion type on ER response may be related to the variation of size and plasticization effect of counteranions that has altered the transport dynamic of mobile counterions and ion motion-induced interfacial polarization. Graphic abstract: Electro-responsive electrorheological effect of monodisperse poly(ionic liquid) particles shows significant dependence on the type of counterions because the variation of size and plasticization effect of counterions has altered ion transport dynamic and ion motion-induced particle polarization. Highlights: Monodisperse PIL particles with different counterions are synthesized via microwave polymerization. PILs with smaller counterions exhibit higher ER response for PILs with organic counterions or inorganic counterions alone. ER response of PILs with organic counterions has higher temperature sensitivity compared to PILs with inorganic counterions. Counterion type influence on ER response is due to size and plasticization effects of counterions on ion transport dynamic.